ChemInform Abstract: Highly Torquoselective Electrocyclizations and Competing 1, 7‐Hydrogen Shifts of 1‐Azatrienes with Silyl Substitution at the Allylic Carbon. Issue 36 (September 2015) - Ma, Zhi‐Xiong; Patel, Ashay; Houk, K. N.; Hsung, Richard P.
Abstract The reaction of cyclic enaminones to 1‐azatriene intermediates that contain an allylic stereocenter substituted with a silyl group is developed.